Pengaruh Aktivitas Eksklusif Sempadan Pantai Bagi Kehidupan Masyarakat Di Pantai Double-Six - Gracia Luciana Handayani; Putri Kusuma Sanjiwani (JURNAL DESTINASI PARIWISATA, 2020)
The tourism sector has a lot of impact on the economy of Badung Regency, especially in the Province of Bali even though, the ongoing activities of exclusive beach borders that are used for public spaces cannot yet be tolerated.As for the scope of the research, there are exclusive activities carried out by tourism entrepreneurs in the area of ??the beach that are used for exclusive activities, such as: tourist activities, community activities, activities of businesses in the field of tourism, viewpoints of tourists, viewpoints of people who live in villages. Seminyak customary, along with the regency-Badung regulations regarding exclusive activities on the coastline at DTW Double-Six Beach. techniques in collecting data in this study include observation, interviews, literature studies, and also documentation. The purposive sampling method is the technique of determining the informants used. The technique used in the cultivation of the report is a qualitative descriptive analysis. Exclusive activities at Sempadan Pantai carried out by tourism entrepreneurs include: K-Resto, Blue9Beach, The Sand Beach Bar&Grill, Capil Beach Grill&Bar, D’Joglo Beach Bar&Restaurant, The-Camplung Bar&Restaurant, La-Plancha, Bali Juice-Park, Taris-Bali, dan Chiringuito Bar-Grill- Restaurant. This exclusive activity also gives effect to the people who live around the Smeinyak Indigenous Village community, among others in terms of language, how to dress, building a business place, music flow, food and drink, and so forth. Tourism that comes is also presented with attractions that are present / modern eyword: exculsive activity, impact, beach border, public area, double six beach